PENGARUH SOSIALISASI, PELATIHAN DAN SKALA BISNIS TERHADAP KEPATUHAN MEMBUAT LAPORAN KEUANGAN SESUAI STANDAR AKUNTANSI KEUANGAN EMKM (STUDI KASUS PADA UMKM DI KECAMATAN GADING CEMPAKA KOTA BENGKULU) - Ummul Khair; Anggun Setyowati (Universitas Muhammadiyah Bengkulu, 2024)
Financial management is the basis for the smooth running of a business, but there are still many MSME actors who do not realize how important financial recording and bookkeeping are. This study aims to determine the extent to which Socialization, Training and Business Scale Influence Compliance in Making Financial Reports in Accordance with EMKM Financial Accounting Standards. The research method uses quantitative descriptive. The object of this research is Micro, Small and Medium Enterprises in Gading Cempaka District, Bengkulu City. The number of respondents in this study was 32 people. The data collection method used a questionnaire. Based on the data analysis test carried out, it shows that the Socialization variable does not affect Compliance in Making Financial Reports in Accordance with EMKM Financial Accounting Standards with a significance value of 0.554> 0.05, Training has a positive effect on Compliance in Making Financial Reports in Accordance with EMKM Financial Accounting Standards with a value of 0.000 <0.05, Business Scale has a positive effect on Compliance in Making Financial Reports in Accordance with EMKM Financial Accounting Standards with a value of 0.000 <0.05. Keywords: Socialization, Training, Business Scale, Financial Report Compliance, EMKM Financial Accounting Standards